PERILAKU STILISTIKA (DEVIASI MORFOLOGIS) DALAM KUMPULAN PUISI SUTARDJI CALZOUM BACHRI - Naidah Naidah; Asriani Abbas; Kaharuddin Kaharuddin (Journal of Innovation Research and Knowledge, 2023)
Stylistic behavior (Morphological Deviation) In the Collection poetry by Sutardji Calzoum Bachri. The purpose of this study is (1) To identify the form of morphological deviation in the poetry collection of Sutardji Calzoum Bachri based on the pattern of grammatical deviations. (2) To describe the morphological deviation which achieves the purpose of aesthetic effect in a collection of poetry by Sutardji Calzoum Bachri. This study uses a qualitative research type method research which is based on several concepts and principles of qualitative research. The approach used is content analysis. First, the researcher read a collection of poetry by Sutardji Calzoum Bachri, then collected data on the morphological deviations of affixation, reduplication and composition. After the data was collected, the researcher analyzed the form of the morphological deviation based on several patterns of grammatical deviation according to Darwis. Based on the results of this study, it is found that 29 poetry of 69 poetry collections O, Amuk, Kapak by Sutardji Calzoum Bachri had morphological deviations. There are 55 data forms of morphological deviations with various patterns of grammatical deviations. It’s a pattern of deletion by affixes in the form of prefixes, suffixes, confixes, omissions of duplicated words and conjuctions. The Patterns of basic form exchange analogy patterns and syllable order variation patterns. The author found 10 data of morphological deviation shapes that were able to achieve an aesthetic effect with six aesthetic impressions. The six aesthetic impressions are the impression of hope, the impression of loneliness, the impression of hatred, the impression of sadness, the impression of longing, and the impression of anger.